Development of Virtual Oscilloscope using JavaTM programming language - Lee, Chor Win; Afandi, Ahmad (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th-19th May 2005 at Putra Palace Hotel, Kangar.